2010
DOI: 10.1007/s11046-010-9334-1
|View full text |Cite
|
Sign up to set email alerts
|

Acr emonium Species: A Review of the Etiological Agents of Emerging Hyalohyphomycosis

Abstract: Unusual fungal agents that exist environmentally as saprophytes can often lead to opportunistic infections. Hyalohyphomycosis is a group of fungal infections caused by fungi characterized by hyaline septate hyphae and can infect both immunocompetent as well as immunocompromised patients. Many a times it becomes difficult to distinguish a pathogenic and a contaminant fungus, because many such agents can assume clinical significance depending on circumstances. Subcutaneous and invasive fungal infection due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 72 publications
1
50
0
4
Order By: Relevance
“…The last 2 decades have witnessed a steady increase in the spectrum of hyaline fungi incriminated as opportunistic pathogens in immunocompromised patients (5,14,28). Many soil saprobes and plant pathogens with no obvious pathogenic potential have now emerged as etiologic agents under a variety of clinical conditions, thus posing new diagnostic and therapeutic challenges (38).…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…The last 2 decades have witnessed a steady increase in the spectrum of hyaline fungi incriminated as opportunistic pathogens in immunocompromised patients (5,14,28). Many soil saprobes and plant pathogens with no obvious pathogenic potential have now emerged as etiologic agents under a variety of clinical conditions, thus posing new diagnostic and therapeutic challenges (38).…”
Section: Case Reportmentioning
confidence: 99%
“…Although Aspergillus and Fusarium are two major pathogenic filamentous genera, the role of Acremonium spp. is also being increasingly recognized in both localized and systemic infections (5,7,28). In immunocompetent individuals, keratitis, endophthalmitis, mycetoma, onychomycosis, or cutaneous infections are the most familiar forms of localized infections (5, 38).…”
Section: Case Reportmentioning
confidence: 99%
“…Das et al, reported a total of 17 cases between 1971 and 2010 of worldwide clinical ocular infections caused by different species of acremonium, which described symptoms including keratitis and endophthalmitis in these patients. 3 Alfonso et al reported four cases of acremonium fungal keratitis associated with laser-assisted in situ keratomileusis (LASIK) that were performed by different surgeons during the same time period in the same operating room. 4 Aside from these instances, until recently, there had been no other reported case series of acremonium fungal keratitis.…”
Section: Introductionmentioning
confidence: 99%
“…They are associated with a wide spectrum of clinical diseases, including both localized and disseminated infections in immunocompetent and immunocompromised hosts (4,6,12,14,15). Acremonium species are also pathogenic to other fungi (mycopathogenic) and have been used as biological controls for fungal plant pathogens (3,13).…”
mentioning
confidence: 99%
“…Unlike Acremonium, however, this species has not been associated with disease in humans in spite of its abundance in the natural environment (10). Acremonium and Lecanicillium share many morphological features, including hyaline colony, cottony texture, and similar arrangement of conidia and conidiophores, that make morphological distinction between the two fungal taxa challenging (4,7,9). We investigated a cluster of Acremonium and Lecanicillium isolates recovered from tissues removed from patients during orthopedic surgery at hospital A.…”
mentioning
confidence: 99%